The Romanovs : the final chapter - Massie, Robert K., 1929- (London : Jonathan Cape, 1995)
Family-Russia History, forensic osteology. Pretenders to the throne.
I. The bones. Down twenty-three steps -- Approved by Moscow -- Let me find nothing -- A character from Gogol -- Secretary Baker -- Curious about death -- The Ekaterinburg conference -- At the frontiers of knowledge -- Dr. Maples versus Dr. Gill -- Ekaterinburg confronts its past -- Investigator Soloviev -- Burying the Tsar -- II. Anna Anderson. The imposters -- The claimant -- A matter of family honor -- These people have no standing -- As good as the people using it -- The cleverest of the four children -- III. The survivors. The Romanov emigres -- IV. The Ipatiev house. Seventy-eight days.
Includes bibliographical references and index
Keywords: Nicholas -- II, -- Emperor of Russia, -- 1868-1918 -- Assassination; Nicholas -- II, -- Emperor of Russia, -- 1868-1918 -- Family; Russia -- History -- Nicholas II, 1894-1917.; Forensic osteology -- Russia; Pretenders to the throne -- Russia; Forensic osteology -- Russia; Nicholas II, Emperor of Russia -- Assassination; Nicholas II, Emperor of Russia -- Family; Pretenders to the throne -- Russia; Russia -- History -- Nicholas II, 1894-1917.